Influencia del español en el sistema vocálico shuar: vocales susurradas - Valeš, Miroslav (2017)
The objective of the following paper is to present a study about the voiceless vowels in Shuar and their decreasing vitality. The hypothesis of the study presumes that the voiceless vowels disappear due to the influence of Spanish vocalic system. The database for the research was collected in 21 Shuar communities. The study takes into account three extralinguistic factors: age, locality and grade of bilingualism. The conclusion confirms that the contact with Spanish plays an important role in the disappearance of the voiceless vowels as the intensity of contact with Spanish is the most influential factor in their gradual disuse.